Hungarian Monitoring, 19 April 1989 . [Magyar rádiófigyelő], 1989. április 19 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Walesa in Rome - Internal struggles in Yugoslavia - NATO countries' defense ministers meet - French towns and villages come together to save 17 Romanian villages sentenced to destruction Domestic Affairs: - Hungarian Socialist Workers' Party (MSZMP) Political Committee in session: rewriting the constitution, post of president of the republic, elections under discussion - Hungarian-Israeli diplomatic relations - Opposition organizations' roundtable talks coordinated by Independent Lawyers' Forum start today to discuss concepts of the new constitution - Return of four excluded MPs to Parliament - Chancellor Kohl's party welcomes Hungarian removal of Iron Curtain on western border - Gabčíkovo-Nagymaros: earthquake risk Economy: - Industry policy council discusses how to recover from insolvency Külpolitika: - Walesa Rómában - Belső harcok Jugoszláviában - NATO országok védelmi minisztereinek találkozója - Francia városok, falvak fogtak össze 17 pusztulásra ítélt romániai falu megmentéséért Belpolitika: - Ülést tartott az MSZMP PB-a; Az alkotmányozásról, a köztársasági elnök intézményéről és a választásokról tárgyaltak - Magyar-izraeli diplomáciai kapcsolatok - Ma kezdődött az ellenzéki szerveztek kerekasztal-tárgyalása a Független Jogászfórum koordinációjával, amelyen az új alkotmány koncepciójáról is tárgyalnak - A négy kizárt képviselő visszavétele a pártba - Kohl kancellár pártja üdvözli, hogy Magyarország lebontja a műszaki zárat nyugati határán - Bős-Nagymaros: a földrengés veszélyeztetettség kérdése Gazdaság: - Az Iparpolitikai tanács ülésén a csődből való kilábalás lehetőségeiről tárgyaltak